(3JGQjN GHf CHj NjKeIs - (3GHf CHj NKjeI CHj HcQ CMeO Hf RgjQ (B((3CHj NKjeI (B)(3Hf MQH Hf TOGO GdfSGFjs
(3ChdgG (B:s
(3eQI Hf TQGMHjd GdWjH s
(3BNQgG (B:s
(3jfJgi GKfGA JQLeI (B" (3YGeQ Hf TQGMHjd GdTYHi (B" (3Hbhdg (B: (3MOKfG eMeO GHf jRjO bGd MOKfG MaU Hf ZjGK Ke jbhd gPG hbO RhMeJ ai GdQMe acSa dh cfJ fSjL hMOi s
(3bWYI UZjQI ef JGQjN GHf CHj NjKeIs
(3fSNI Ydi Qb ZRGd hHChdgG SeGY dbGSe Hf CUHY SfI (B322 (3hbQGAI SfI (B320s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(2671(3c(B) s
Keywords: (3GdJGQjNs